Development of diagnostic microsphere-based immunoassays for Heartland virus - Basile, Alison Jane; Horiuchi, Kalanthe; Goodman, Christin H.; Kosoy, Olga; Panella, Amanda J.; Velez, Jason O.; Pastula, Daniel M.; Brault, Aaron C.; Staples, J. Erin; Calvert, Amanda E. (Journal of clinical virology, 2021)
•IgM and IgG microsphere immunoassays for Heartland virus were developed.•Both assays demonstrated >95 % sensitivity, specificity and accuracy.•Anti-HRTV IgM and anti-HRTV IgG was detected in human serum.•The HRTV microsphere immunoassays are intended as first-line diagnostic tools. Background. Heartland virus (HRTV), a recently reclassified member of the genus Bandavirus, family Phenuiviridae, was first isolated in 2009 from a Missouri farmer exhibiting leukopenia and thrombocytopenia with suspected ehrlichiosis. Since then, more HRTV cases have been diagnosed, and firstline laboratory diagnostic assays are needed to identify future infections Objectives. We sought to develop rapid and reliable IgM and IgG microsphere immunoassays (MIAs) to test sera of patients suspected of having HRTV infection, and to distinguish between recent and past infections. Study design. Heartland virus antigen was captured by an anti-HRTV monoclonal antibody covalently bound to microspheres. Antibodies in human sera from confirmed HRTV-positive and negative cases were reacted with the microsphere complexes and detected using a BioPlex® 200 instrument. Assay cutoffs were determined by receiver operator characteristic analysis of the normalized test output values, equivocal zones for each assay were defined, and sensitivities, specificities, accuracies, and imprecision values were calculated. Results. Sensitivities, specificities and accuracies of the IgM and IgG MIAs were all >95 %. Both tests were precise within and between assay plates, and cross-reactivity with other arboviruses was not observed. Conclusions. HRTV IgM and IgG MIAs are accurate and rapid first-line methods to serologically identify recent and past HRTV infections.